Lipid Profiles From Fresh Biofilms Along a Temperature Gradient on a Hydrothermal Stream at El Tatio (Chilean Andes), as a Proxy for the Interpretation of Past and Present Biomarkers Beyond Earth - Megevand, Valentine; Carrizo, Daniel; Lezcano, María Ángeles; Moreno-Paz, Mercedes; Cabrol, Nathalie A.; Parro, Víctor; Sánchez-García, Laura (Frontiers in Microbiology, 2022)
Hydrothermal systems and their deposits are primary targets in the search for fossil evidence of life beyond Earth. However, to learn how to decode fossil biomarker records in ancient hydrothermal deposits, we must first be able to interpret modern biosignatures unambiguously, their distribution patterns, and association with physicochemical factors. We investigate the molecular and isotopic profile of microbial biomarkers along a thermal gradient (from 29 to 72°C) in a hot spring (labelled Cacao) from El Tatio, a geyser field in the Chilean Andes with abundant opaline silica deposits resembling the nodular and digitate structures discovered on Mars. As a molecular forensic approach, we focused on the analysis of lipid compounds bearing recognized resistance to degradation and potential to reconstruct the paleobiology of an environment in a broader temporal scale than other, more labile, biomolecules. By exploiting the lipid biomarkers´ potential to diagnose biological sources and carbon fixation pathways, we reconstructed the microbial community structure and its ecology along the Cacao hydrothermal transect. The taxonomic adscription of the lipid biomarkers was qualitatively corroborated with DNA sequencing analysis. The forensic capacity of the lipid biomarkers to identify biosources in fresh biofilms was validated down to the genus level for Roseiflexus, Chloroflexus, and Fischerella. We identified lipid biomarkers and DNA of a number of new cyanobacterial species in El Tatio, and reported the first detection of Fischerella biomarkers at a temperature as high as 72ºC. This, together with ecological peculiarities and the proportion of clades being characterized as unclassified, illustrate the ecological singularity of El Tatio and strengthen its astrobiological relevance. The Cacao hydrothermal ecosystem was defined by a succession of microbial communities and metabolic traits associated with a high (72ºC) to low (29ºC) temperature gradient that resembled the inferred metabolic sequence events from the 16S rRNA gene universal phylogenetic tree from thermophilic to anoxygenic photosynthetic species and oxygenic phototrophs. The locally calibrated DNA-validated lipidic profile in the Cacao biofilms provided a modern (molecular and isotopic) endmember to facilitate the recognition of past biosources and metabolisms from altered biomarkers records in ancient silica deposits at El Tatio analogous to Martian opaline silica structures.